2017
DOI: 10.15587/1729-4061.2017.117315
|View full text |Cite
|
Sign up to set email alerts
|

Study of the сhemical composition of cranberry and the use of berries in food technology

Abstract: Представлено дослідження хімічного скла-ду ягід журавлини. Визначено фракційний склад органічних кислот, цукрів та фенольних речовин, що містяться в продуктах переробки журавли-ни. Експериментально підтверджено позитивний вплив ферментативного каталізу на вилучення фенольних речовин та якість соку з журавлини. Встановлені раціональні умови проведення фер-ментативного каталізу. Запропоновано комплек-сну переробку ягід журавлини з використанням соку в технології фруктових соусів, а вичавок сокового виробництва -… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The mechanisms of action underlying the anticancer effect of kaempferol are based on inhibition of the cell cycle in the G2/M phase to prevent tumor growth and proliferation, as well as induction of apoptosis by acting on different cell signaling pathways. Several in vitro studies have also observed its anti-angiogenic effect and anti-metastatic, inhibiting VEGF production and decreasing the expression of markers that are involved in epithelial-mesenchymal transition (EMT) at a dose of 0.1 µM in MDA cell lines [83,84]. Pharmacokinetic studies that were performed in rats determined that the bioavailable fraction of this compound after oral doses was 2% of the total administered [85].…”
Section: Kaempferolmentioning
confidence: 99%
“…The mechanisms of action underlying the anticancer effect of kaempferol are based on inhibition of the cell cycle in the G2/M phase to prevent tumor growth and proliferation, as well as induction of apoptosis by acting on different cell signaling pathways. Several in vitro studies have also observed its anti-angiogenic effect and anti-metastatic, inhibiting VEGF production and decreasing the expression of markers that are involved in epithelial-mesenchymal transition (EMT) at a dose of 0.1 µM in MDA cell lines [83,84]. Pharmacokinetic studies that were performed in rats determined that the bioavailable fraction of this compound after oral doses was 2% of the total administered [85].…”
Section: Kaempferolmentioning
confidence: 99%
“…Hexanal, pentanal, (E)-2-heptenal, (E)-2-hexenal, (E)-2-octenal, (E)-2-nonenal, ethyl 2methylbutyrate, β-ionone, 2-methylbutyric acid, and octanal were mainly contributing to the cranberry aroma. Khomych et al detected 54 aromatic compounds in cranberry juice [84]. Twenty-three alcohols (41.2% of total concentration) were predominant in cranberry juice, followed by eight acids (40.7%), ten aldehydes (1.7%), five ketones (2.2%), five ethers (1.4%), three lactones, and each heterocyclic and unidentified compound (less than 1% each).…”
Section: Cranberrymentioning
confidence: 99%